61. PREIMPLANTATION GENETIC TESTING FOR MONOGENIC DISEASE OF SPINAL MUSCULAR ATROPHY BY MULTIPLE DISPLACEMENT AMPLIFICATION: 11 UNAFFECTED LIVEBIRTHS. (August 2019) - Chen, D.; Fu, Y.; Shen, X.; Huang, W.; Zhou, C.
Abstract : Introduction: PGT-M has become an effective method for providing couples with the opportunity of a pregnancy with a baby free of spinal muscular atrophy (SMA). Multiple displacement amplification (MDA) overcome the innate dilemma of very limited genetic material available for PGT-M. This study mainly evaluated the use of MDA, combined with haplotype analysis and mutation amplification, in preimplantation genetic testing for monogenic disease (PGT-M) for families with SMA. Material and methods: MDA was used to amplify the whole genome from single blastomeres or trophectoderm (TE) cells. Exon 7 of the survival motor neuron gene 1 (SMN1) and eleven STRs markers flanking the SMN1 gene were incorporated into singleplex polymerase chain reaction (PCR) assays on MDA products. Results: Sixteen cycles (19 ovum pick-up cycles) of PGT-M were initiated in 13 patients. A total of 141 embryos were diagnosed: 90 embryos were biopsied at the cleavage stage and 51 embryos were biopsied at the blastocyst stage. MDA was successful on 94.44% (85/90) of the single blastomeres and on 92.16% (47/51) of the TE cells. And the PCR efficiency were 98.4%(561/570) and 100%(182/182), respectively. In addition, the average allele drop-out (ADO) rates were 13.3%(60/392) and 9.8% (11/112), respectively. The results for SMN1 exon 7 were all matched with haplotype analysis, which allowed an accurate diagnosis of 93.62% (132/141) embryos. Twelve families had unaffected embryos available for transfer and a total of 38 embryos were transferred in 20 embryo transfer cycles. Eight transfers were successful, resulting in an clinical pregnancy rate of 40%(8/20) and an implantation rate of 28.95%(11/38). Finally, 11 healthy babies were born. Among them, 5 patients were singleton live births and and 3 patients had twin births. Conclusion: Careful handling during the MDA procedure can improve subsequent PCR efficiency and reduce the ADO rate. We suggest that this protocol is reliable for increasing the accuracy of the PGT-M for SMA.